2019
DOI: 10.3390/environments6040043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tourism Impacts on Cultural Ecosystem Services

Abstract: Parks and protected areas are recognized for the important ecosystem services, or benefits, they provide society. One emerging but understudied component is the cultural ecosystem services that parks and protected areas provide. These cultural ecosystem services include a variety of benefits, such as cultural heritage, spiritual value, recreation opportunities, and human health and well-being. However, many of these services can only be provided if people visit these parks and protected areas through tourism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Damage to natural resources, although reported infrequently compared to the other outcome variables, occurred in some of the same locations where visitors reported positive outcomes. This suggests that some level of natural resource impact may even enhance overnight users' positive experiences (e. g. visitor-created social trails), but begs us to question at what point those impacts caused by recreationists will be so severe that it negates the positive outcomes gained in these locations (Taff et al 2019). With these results in mind, managers may be able to increase monitoring efforts and management strategies that facilitate the positive outcomes within the SLL area, while potentially mitigating some of the negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damage to natural resources, although reported infrequently compared to the other outcome variables, occurred in some of the same locations where visitors reported positive outcomes. This suggests that some level of natural resource impact may even enhance overnight users' positive experiences (e. g. visitor-created social trails), but begs us to question at what point those impacts caused by recreationists will be so severe that it negates the positive outcomes gained in these locations (Taff et al 2019). With these results in mind, managers may be able to increase monitoring efforts and management strategies that facilitate the positive outcomes within the SLL area, while potentially mitigating some of the negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several maps were created using these data, including individual point density heat maps (Brown & Weber 2011) of each positive and negative outcome, and maps of all positive outcomes combined and all negative outcomes combined. These maps were analysed visually and compared to each other to better understand the spatial relationships between the positive and negative outcomes of overnight users (Steinberg & Steinberg 2015). Finally, in an effort to further understand these spatial relationships and to advance the application of PPGIS methodologies to visitor outcomes (e. g., Pietilä 2017), we used percentages of positive and negative outcomes experienced through overnight backcountry recreation within or outside the Recommended Wilderness boundary, distributed across the String and Leigh Lakes area.…”
Section: Ppgis Data Analysismentioning
confidence: 99%
“…Taff and colleagues [51] in this Special Issue, have shown that a large network of informal trails devalues the perception of a landscape for tourist/recreational activity more than trampled/degraded vegetation. The implication was that their survey respondents perceived over-use by people (visitors).…”
Section: The Trouble With Tramplingmentioning
confidence: 99%
“…Conflicting views arise on other issues, such as tour guides who lament the lack of deer along hiking trails, and managers' concerns that increased deer populations are having a negative impact on vegetation. Taff et al [5] discuss the cultural benefits of natural areas to humans, such as emotional well-being, which can only be realized by visiting such areas, and the impacts on the environment that can accrue from such visits.…”
Section: Highlightsmentioning
confidence: 99%